The Causal Relation between Energy Consumption, Carbon Dioxide Emissions, and Macroeconomic Variables in Somalia - Zakarie Abdi Warsame; Maria Mohamed Ali; Liban Bile Mohamed; Farhia Hassan Mohamed (International Journal of Energy Economics and Policy, 2023)
This study investigated the relationship between energy consumption, carbon dioxide emissions, and macroeconomic variables in Somalia with data spanning from 1990 to 2019 using ARDL model. The study found a negative long-run relationship between carbon dioxide emissions and energy consumption in Somalia, suggesting that improving access to clean energy can reduce the gradual rise of carbon dioxide emissions. The study also found that rising industrial value-added had a significant positive impact on energy consumption. Furthermore, findings from Cholesky's variance decomposition showed that 13.13% of future fluctuations in energy consumption are due to shocks in carbon dioxide emission, 33.63% of future fluctuations in carbon dioxide emissions are due to shocks in energy consumption, 40.63% of future fluctuations in industrialization are due to shocks in energy consumption and 41.23% of future fluctuations in population are due to shocks in energy consumption. There was evidence of a bidirectional causality between: energy consumption and population. The study suggests adding renewable energy technologies to the energy portfolio. This would help reduce reliance on unstable energy sources and reduce the chance that changes in commodity prices will interrupt the energy supply, which eventually would help reduce the effects of climate change.